Long-term results of guided tissue regeneration therapy with non-resorbable and bioabsorbable barriers: I. Class II furcations - Eickholz, Peter; Kim, Ti-Sun; Holle, Rolf; Hausmann, Ernest (Journal of periodontology, 2001)
The aim of this 5-year follow-up study was to clinically and radiographically evaluate the long-term results after guided tissue regeneration (GTR) therapy of Class II furcation defects using non-resorbable and bioabsorbable barriers.
Gesehen am 12.03.2021